Support for Child Education Post-Divorce - Majid, Ikhwanuddin Abdul; Sesmita, Jeniver Tri; Faraditsi, Fauzia; Fitri, Rika; Daulad, Ahmad (Samara: Journal of Islamic Law and Family Studies, 2024)
Most people who have experienced divorce no longer prioritize supporting their children's education. They become busy with their new family, ignoring the needs of their children who need love, education, and other needs. This research aims to analyze children's educational support after divorce using a qualitative case study approach. Data was collected through document analysis, including court records, local policies, educational agency reports, and statistical data related to children's education in the area studied. Direct observations were also carried out to understand environmental conditions and the situation of children affected by divorce. The research results show that post-divorce child education support has not been fully implemented. Most divorced parents do not provide adequate support, which causes some children to be forced to stop going to school. Thematic analysis revealed that economic factors, parents' lack of understanding about the importance of education, as well as the lack of policies that support children's educational rights after divorce, contributed to the lack of educational support for these children. These findings emphasize the need for more effective interventions in the form of policies and programs that support the continuity of children's education after divorce.